RESEARCH ON THE PROCESS OF ADSORPTION OF PETROLEUM PRODUCTS BY INORGANIC SORBENTS - S. T. Almagambetova; A. A. Ersaynova; S. . Zamirbek (Алматы технологиялық университетінің хабаршысы, 2021)
The article examines the sorption capabilities of sorbents for water-soluble petroleum products, as well as the mechanism of adsorption in the practical use of sorbents in water purification processes. The process of adsorption of petroleum products and some ions with inorganic sorbents is considered. The study revealed: 1 gram of sorbent absorbs 15-18 grams of oil, which contributes to the effective fight against oil spills in the aquatic environment. It is recommended to use rice husk as an effective sorbent.